Exploring Secondary English Teacher’s Belief Towards Vocabulary Learning For Young Learners: An Interview Study - Sihombing, Bela Ardianti; Putri Kamalia Hakim; Iwan Ridwan (Universitas Negeri Medan, 2024)
This study looks into one secondary English teacher's beliefs about vocabulary learning for young learners and the contextual factors affecting it, aiming to understand how those both influence her teaching practices. The research uses qualitative methods, specifically interview study, to gather detailed insights into teacher’s views, strategies, and the factors that affect her approach to teaching vocabulary. The findings are that the teacher emphasized the role of handwriting in vocabulary retention, believed in the effectiveness of contextual learning for vocabulary acquisition, and considered textbooks essential tools in vocabulary teaching. Additionally, the study identifies key contextual factors, including the teacher's perceptions of vocabulary learning, teacher’s education, collaboration with colleagues, and the challenges faced in the classroom. The study concludes that a teacher's beliefs and contextual factors significantly shape her vocabulary teaching practices for young learners. Keywords: Teacher beliefs, Vocabulary learning, Contextual Factors